Everyday justice: legal aid for Jewish Displaced Persons, Germany, 1945-1950 - Brot, Rivka (Holocaust and genocide studies, 2022)
Welfare workers volunteering with the American Jewish Joint Distribution Committee (JDC), a Jewish welfare organization, delivered crucial legal assistance to Holocaust survivors gathered in displaced persons (DP) camps in the American Zone of occupied Germany; however, today their story is largely forgotten. Their legal aid program embodied a unique relationship between social work and law. JDC relief workers developed a legal consciousness in response to the many injustices they witnessed in the DP camps, which allowed them to identify the gap between the basic support provided by relief programs, and the actual needs of the DPs. From this awareness they gradually developed a program of legal welfare, assisted Jews in their daily interactions with Americans and Germans, provided them with legal instruction and education, and protected them when conflicts arose. These JDC volunteers were fueled by a sense of moral responsibility and compassion for the Jewish DPs, who were forced to live in a foreign and often hostile environment. Remarkably, this story has largely been neglected in Holocaust scholarship, though the archives have yielded hundreds of reports by JDC welfare workers, as well as the papers of Oskar Mintzer, a key figure in the creation of the JDC’s legal aid program. The JDC was at the forefront of an unprecedented humanitarian crisis, and this aspect of its work represents a forgotten milestone in the development of a more holistic approach to refugee assistance and support. This study offers a starting point for further research in order to better understand humanitarian aid for asylum seekers, DPs, and refugees in the twenty-first century.